2017
DOI: 10.7454/jvi.v5i2.109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Behaviour of E-learning Users by Unified Teory of Acceptance and Use of Technology (UTAUT) Model A Case Study of Vocational Education in Halu Oleo University

Abstract: E-learning (EL) as a supporting tool in learning process has increasingly developed because the implementation of the tool will be helpful for both lecturers and students to be more interactive in delivering materials and to evaluate learning outcomes. Analysis of the user’s behavior was required to measure the success rate of the implementation of e-learning. One of the models used in the present study was Unified Theory of Acceptance and Use of Technology (UTAUT). The model was designed to explain the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
2
6
1
Order By: Relevance
“…This contradicts the finding of Venkatesh et al (2003) in UTAUT model. Nonetheless, the findings of this study is similar in other technology adoption model findings (i.e: TAM; Davis, 1989 and TAM2;Venkatesh & Davis, 2000) and recent past studies (i.e : Bharati et al, 2018;Guest et al, 2018 andJaya et al, 2017). The result indicates that MARLCardio is easy to use and does not require a lot of mental effort to comprehend the usage.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This contradicts the finding of Venkatesh et al (2003) in UTAUT model. Nonetheless, the findings of this study is similar in other technology adoption model findings (i.e: TAM; Davis, 1989 and TAM2;Venkatesh & Davis, 2000) and recent past studies (i.e : Bharati et al, 2018;Guest et al, 2018 andJaya et al, 2017). The result indicates that MARLCardio is easy to use and does not require a lot of mental effort to comprehend the usage.…”
Section: Discussionsupporting
confidence: 89%
“…Many past studies' findings show that PE had a significant impact towards UB of proposed technology. It is proven in studies by Guest et al (2018), Paulo et al (2018), Jaya et al (2017), Abdullah & Ward (2016) and Mou et al (2016). Unexpectedly, the present study found a contrary finding.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations